Terror and territory: A spatio-temporal analysis of ISIL - Strider, Robert Riley (2017)
The Islamic State of Iraq and the Levant (ISIL), alternatively the Islamic State of Iraq and Syria (ISIS), is one of many non-state organizations that resulted from the extensive foreign intervention in the Middle East leading up to current conflicts there. Like the wider network that it used to be part of, ISIL is considered to be a great threat to modern first world countries. Using data from the Global Terrorism Database (GTD), this paper analyzed the relationship between the amount of territory ISIL held from June 2014 to December 2015 and the attacks it carried out in that time, using Standard Deviational Ellipses to analyze directional orientation and distribution density of the attacks. The results showed that there was a slight correlation between significant land loss and increases in attacks in the following quarter